KILKA UWAG O SĄDOWNICTWIE ADMIRALICJI W ANGLII - Marzec, Łukasz (Zeszyty Prawnicze, 2017)
Some Remarks on the Admiralty Jurisdiction in England Summary The Court of Admiralty was a significant element of the English judicial system that operated outside common law. It offered a quick and effective procedure, more efficient and suitable to fit mercantile cases. Many of its judges were doctors of civil law and members of the elitists organization: Doctors’ Commons. Some of the court’s jurisdiction was based on the Roman law, which was one of the reasons for envy and jealousy among the common law judges headed by Sir Edward Coke. The sentences of the court were permanently blocked by common law judges, which resulted in many complaints made by Lord Admiral to the King and Parliament. The Court of Admiralty was undoubtedly the most powerful English judicial institution using the rules of Roman law in its practice. One of the examples presented in this paper is the question of the maritime loan secured on the ship called bottomry or respodentia, based on the pecunia traiecticia and foenus nauticum.